An in vitro evaluation of pH variations in calcium hydroxide liners - Subramaniam P; Konde S; Prashanth P (Wolters Kluwer Medknow Publications, 2006)
The purpose of this present study was to determine the pH changes of five different commercially available calcium hydroxide liners and variations of pH at different time intervals. The following commercially available materials were investigated: Dycal (LD Caulk); Calcimol (Vocco Products); calcium hydroxide powder (Deepti Products); Calcimol LC (Vocco Products); Lime-Lite (Pulpdent Corporation). Five samples were prepared from each liner. The pH measurements were recorded at time intervals of 1 h, 24 h, 3 days and 7 days after mixing of the liner. The pH variations of each material at the given time intervals were recorded and the means were calculated. Comparison of the mean values at all time intervals with the statistical analysis showed significantly high differences ( P < 0.001) between pH values induced by each material at all time intervals. Among the water-insoluble products, Dycal had the strongest alkaline effect after 7 days interval. The materials that chemically hardened produced higher pH values than materials that hardened by a visible light source after 7 days.